Peran Penting Akuntansi dalam Rumah Tangga - Wahyuni, Sri; Marlina, Marlina; Wardhani, Neng Sri (General Ledger : Jurnal Studi Ilmu Akuntansi dan Keuangan, 2024)
AbstractIn this study, researchers tried to reveal the important role of accounting in the household and budget planning in the household. How do respondents implement household accounting and manage their finances regarding 4 (four) important things, namely: budgeting, recording, decision making and long-term planning. This research revealed the accounting practices in the households of 20 respondents with the criteria of having a permanent job with a minimum educational background of Bachelor's degree, being married and having children who live in Medan City. The focus of discussion and observation was attempted to answer problems regarding respondents' understanding of household accounting practices. The qualitative method used in this research uses the theoretical basis of phenomenological studies. This research will discuss human behavior, especially in managing and planning family finances, where the data is obtained from information and statements from the objects studied. The differences in accounting practices in households carried out by respondents are based on the level of knowledge and understanding they have regarding accounting, geographical area and employment status. However, even though almost half of the respondents do not have financial records, almost all respondents have savings to protect them for the future.AbstrakPada penelitian ini, peneliti mencoba mengungkap tentang peran penting akuntansi dalam rumah tangga serta perencanaan penganggaran dalam rumah tangga. Bagaimana cara responden melakukan penerapan akuntansi rumah tangga dan mengelola keuangan mereka mengenai 4 (empat) hal penting yaitu: penganggaran, pencatatan, pengambilan keputusan dan perencanaan jangka panjang. Penelitian ini mengungkap praktek akuntansi di rumah tangga pada 20 responden dengan kriteria memiliki pekerjaan tetap berlatar belakang pendidikan minimal S1, sudah bekeluarga dan memiliki anak yang berdomisili di Kota Medan. Adapun fokus pembahasan dan observasi diupayakan untuk menjawab permasalahan tentang pemahaman responden terhadap praktik akuntansi rumah tangga. Metode kualitatif digunakan dalam penelitian ini memakai dasar teoritis studi fenomenologi. Penelitian ini akan membahas perilaku manusia khususnya dalam mengelola dan merencanakan keuangan keluarganya, dimana datanya diperoleh dari keterangan dan pernyataan – pernyataan dari obyek yang diteliti. Perbedaan praktik akuntansi dalam rumah tangga yang dilakukan responden dilatarbelakangi oleh tingkat pengetahuan dan pemahaman yang dimiliki terhadap akuntansi, daerah geografis dan status pekerjaan. Tetapi walaupun hampir setengah responden tidak memiliki catatan keuangan hampir dari seluruh responden memiliki tabungan untuk berjaga dimasa yang akan datang.